Urban Fertilizer Ordinances in the Context of Environmental Horticulture and Water Quality Extension Programs: Frequently Asked Questions - Michael Dukes; Lisa Krimsky; Mary Lusk; Laurie E Trenholm; Joseph B Unruh; Michelle Atkinson; Rao Mylavarapu; Caroline R Warwick (EDIS)
Excess nitrogen (N) and phosphorus (P) in water bodies are a leading cause of water quality degradation statewide. More than 50 Florida counties and municipalities now have formal fertilizer ordinances, which in some cases include fertilizer blackouts, or bans on the usage of N and P fertilizers during certain times of the year. This 8-page document provides information on the underlying issues of fertilizer use, with an emphasis on an urban setting, and outlines the current state of the science on urban fertilizers and water quality in Florida. Written by Michael D. Dukes, Lisa Krimsky, Mary Lusk, Laurie Trenholm, Bryan Unruh, Michelle Atkinson, and Rao Mylavarapu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2020. https://edis.ifas.ufl.edu/ae534